(untitled) (Bangladesh Journal of Medical Microbiology, 2023)
Background: Extra-pulmonary tuberculosis (EPTB) is a diagnostic and therapeutic challenge due to the paucity of suitable rapid diagnostic tools. Objectives: The aim was to assess the frequency of detection of Mycobacterium tuberculosis using Xpert MTB /RIF assay among the extra-pulmonary and non-sputum respiratory samples (NSRS) along with demographic profile, life style variables and proportion of Rifampicin resistant TB among those specimens. Methodology: This cross-sectional retrospective study was conducted at National Tuberculosis Reference Laboratory (NTRL) from January 2018 to December 2018 for period of 1 year. Total 3918 extra-pulmonary and non-sputum respiratory samples from suspected TB patients were enrolled. Detection of Mycobacterium tuberculosis and Rifampicin resistance was performed by Xpert MTB /RIF assay and culture in both liquid and solid media. Results: Among 3918 samples, 3152 were new cases and 766 were previously treated TB cases. A total of 853 (21.77%) MTB were detected by Xpert MTB /RIF assay. Among them, 713 (83.59%) were extra-pulmonary and 140 (16.41%) were non-sputum respiratory samples. Lymph node (LN) aspirates and tissues were the most frequent (37.9 and 9.9%) samples of EPTB. The proportion of RR cases among EPTB was 2.8% and 6.3% among new and previously treated cases. And 2.6% and 11.1% among NSRS new and previously treated cases respectively. Conclusion: This study will give an insight of EPTB and NSRS profile with a view to diagnostic and therapeutic approach in Bangladesh. Bangladesh Journal of Medical Microbiology, January 2023;17(1):21-28